(untitled) (Superficies y Vacío, 2012)
Boron nitride (BN) nanostructures are chemically inert, electrically insulating, and potentially important in mechanical applications. Using borazine (B3N3H6) gas as chemical precursor and the Chemical Vapor Deposition (CVD) BN nanostructures were obtained at a rate of 80.5 g/h, with sizes ranging between 20 and 50 nm. Their structure, morphology and chemical composition were analyzed by: X-ray, TEM, EDS, FT-IR, EELS and XPS. Taken altogether, the results obtained show that all the nanostructured material is stoichiometric BN with hexagonal and rhombohedral structure.